Chemical Properties of “Jati Unggul Nusantara” Teak Wood from Gunungkidul - Lukmandaru, Ganis; Pratama, Ardhan Wira; Sutapa, Johanes Pramana Gentur; Sunarta, Sigit; Irawati, Denny; Pujiarti, Rini; Arisandi, Rizki (Wood Research Journal, 2024)
Jati Unggul Nusantara (JUN) trees show a fast-growing characteristic and a possibility to be harvested in short rotation. This study aims to determine the chemical properties of 8-year-old JUN tree parts. Three individual trees were felled from Paliyan, Gunungkidu, Yogyakarta, Indonesia. The tree parts were observed vertically (i.e., the bottom, center, top, branches, and twigs) and radially (i.e., sapwood and heartwood of the trunk). The result showed that the average content of cell wall components of extractive-free wood, i.e., hemicellulose, α-cellulose, and lignin, were 20.38~25.71%, 41.88~49.10%, and 26.46~29.85%, respectively. Furthermore, successive extractive measurements showed that ethanol-toluene and hot-water soluble extracts (based on dry wood) were at the levels of 3.01~7.58% and 1.85~3.09%, respectively. The ash content, silica content, and pH values were 0.48~0.82%, 0.13~0.37%, and 5.89~7.51%, respectively. By an analysis of variance, significant differences between the sapwood and the heartwood were observed in ethanol-toluene extractive, lignin, holocellulose, and cellulose contents. The differences among tree parts did not show any significant effect on the hot-water soluble content. Significant differences between the main stem and branches or between the main stem and twigs were observed in most chemical properties.